2018
DOI: 10.5114/jcb.2018.76748
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance during interstitial brachytherapy: in vivo dosimetry using MOSFET dosimeters

Abstract: PurposeBrachytherapy procedure may result in acute tissue reactions like edema, causing deviations between planned and measured doses. The rationale for in vivo dosimetry in interstitial brachytherapy is to assess the accuracy of the delivered dose in comparison with the dose calculated by the treatment planning system (TPS).Material and methodsOne single computer tomography (CT) dataset was used for brachytherapy planning, taken within 24 hours after implantation. In vivo interstitial measurements with micro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Their study showed that the overestimations of MOSFET (uncorrected for energy response) to TPS dose values were 2-7% for the end-to-end measurements in HDR prostate and head and neck implantations. Inaccuracy of the MOSFET detectors (±4%) was reported, and the deviations between the planned and measured dose values were markedly influenced by the tube applicator geometry and the positioning of the patient during irradiation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Their study showed that the overestimations of MOSFET (uncorrected for energy response) to TPS dose values were 2-7% for the end-to-end measurements in HDR prostate and head and neck implantations. Inaccuracy of the MOSFET detectors (±4%) was reported, and the deviations between the planned and measured dose values were markedly influenced by the tube applicator geometry and the positioning of the patient during irradiation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Dose veri cation measurements were performed using Gafchromic EBT3 lm (Ashland Specialty Ingredients, NJ, USA lot#09071703 and #04171901) and three MOSFET TM detectors to be described in the following section. The feasibility and e ciency of MOSFET detectors were con rmed in real-time invivo dosimetry for brachytherapy by previous researchers [20,21].…”
Section: Methodsmentioning
confidence: 98%
“…Table 2 provides an overview of the reported clinical studies of IVD for brachytherapy. Most (20/27) of the studies reported on integrated dose from point detectors (e.g., thermoluminescent dosimeters [41] , [42] , [43] , [44] , [45] , metal-oxide semiconductor field-effect transistors (MOSFETs) [46] , [47] , [48] , optically stimulated luminescence detectors [49] , diodes [50] , [51] , [52] , glass detectors [53] , plastic scintillators [54] , and alanine dosimeters [52] , [55] ) for different treatment sites. These studies reported maximum deviation between measured and planned dose ranging from a few percent to more than 100%.…”
Section: Methods For Ivdmentioning
confidence: 99%
“… MR scans acquired just before and after the treatment. Reported uncertainty 5.0% (k = 1) 2018 Melchert et al [46] BR, TH, HN MOSFET 12 ≈ 56.0% Dosimeters inserted into catheters/needles. A long interval between needle implantation and imaging can reduce positioning uncertainties due to edema.…”
Section: Methods For Ivdmentioning
confidence: 99%